2021
DOI: 10.15587/1729-4061.2021.237806
|View full text |Cite
|
Sign up to set email alerts
|

Determining the nutritional value and quality indicators of meat-containing bread made with hemp seeds flour (Cannabis sativa L.)

Abstract: Meat-containing bread with the use of hemp flour has been devised, with the subsequent assessment of its physical and chemical, sensory properties involving the study into the technological indicators of new products. Three experimental formulations for meat-containing bread were developed, which included semi-fat pork, poultry, mechanically deboned turkey, pumpkin pulp, and 8, 10, 12 % of hemp flour. A meat-containing bread from combined raw materials was adopted as control. All samples were evaluated taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
2
2
0
Order By: Relevance
“…Regardless of the amount of ingredients used within the study groups, the pH remained virtually unchanged ( p > 0.05), and the pH values of the analyzed samples ranged from 6.40 to 6.41 ( Table 2 ). Similar results were obtained by Kotecka-Majcharzak et al [ 21 ] in pork meatballs with a varied amount of hemp cake and by Bozhko et al [ 38 ]. In turn, Kerner et al [ 5 ] showed the higher pH of pork burgers with the addition of dried and pressed hemp cake and sweet grass.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Regardless of the amount of ingredients used within the study groups, the pH remained virtually unchanged ( p > 0.05), and the pH values of the analyzed samples ranged from 6.40 to 6.41 ( Table 2 ). Similar results were obtained by Kotecka-Majcharzak et al [ 21 ] in pork meatballs with a varied amount of hemp cake and by Bozhko et al [ 38 ]. In turn, Kerner et al [ 5 ] showed the higher pH of pork burgers with the addition of dried and pressed hemp cake and sweet grass.…”
Section: Resultssupporting
confidence: 89%
“…In our study, it was shown that enrichment of the meat product with hemp products had a beneficial effect on increasing the protein content ( p < 0.05) in group P 1 , with a higher content of hemp seeds compared to group P 2 and the control group ( Table 3 ). Similar results have also been shown by other authors: Zając et al [ 20 ], Bozhko et al [ 38 ], Augustyńska-Prejsnar et al [ 32 ], and Zinina et al [ 18 ], who used high-protein hemp products (hulled hemp seeds, hemp flour, and hemp protein) to enrich meat products. In contrast, Kerner et al [ 5 ] did not observe an increase in protein in a pork burger after the introduction of 2% hemp cake.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Hemp seed processing products are a source of dietary fiber (up to 15 %) [18]. In [19], it is proved that the addition of hemp flour to the recipe of meat-containing products improves the consumer value of products by increasing the content of protein, fat, and mineral elements. It has been experimentally confirmed that the introduction of hemp flour into the composition of meat systems improves their functional and technological indicators.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%